THE EFFECT OF EARLY MOBILIZATION ON THE ACCELERATION OF POSTOPERATIVE WOUND HEALING IN THE SURGICAL INPATIENT WARD OF ACEH BESAR REGIONAL HOSPITAL - Yennizar Yennizar; Nurul Ibrahim; Mela Hayani; Andri Juanda; Maulida Maulida; Nuri Nazari (Getsempena Health Science Journal, 2026)
Post-operative wound healing and length of stay are common problems, due to physiological, psychological, and health care system factors, including pain, physical weakness, fear and anxiety, lack of motivation, and inadequate pre- and post-operative education. Early mobilization is an important non-pharmacological intervention in the patient's recovery process after surgery. This study aimed to determine the effect of early mobilization on the acceleration of postoperative wound healing in the Surgical Inpatient Room of RSUD Aceh Besar. This research used a quantitative method with a quasi-experimental design, applying a one-group pre- test and post-test approach without a control group. The sample consisted of 36 respondents, selected using accidental sampling technique. Data were collected from June 13 to July 18, 2025, using the REEDA observation sheet, which includes five indicators: redness, edema, ecchymosis, discharge, and approximation. The results showed that before the intervention, most respondents were in the slow healing category (94.4%). After the early mobilization intervention, there was a significant decrease in REEDA scores, with 86.1% of respondents falling into the fast healing category. The Wilcoxon Signed-Rank Test showed a Z value of –5.114 and a p-value of 0.000 (p < 0.05), indicating a significant effect of early mobilization on the acceleration of postoperative wound healing.